Developing an intensive reading material for EFL students: A final product - Pratnyawati Nuridi Suwarso; Muhammad Dzulfiqar Praseno (Universitas Bengkulu, 2022)
This research aims at developing the Intensive Reading material for the second-semester English Language Education Program students. It is a Research and Development study that was done by using Reeves’ (2000) Design-Based Research model. Tomlinson’s (1998) definition of learning material is also used as one of the considerations in developing the material since the material needed by the students should contribute to the students’ needs. The needs analysis showed that the intensive reading skills are still considered difficult for some students. Additionally, the content of the product is based on the syllabus and the Outcome Based Education (OBE) curriculum. The researchers develop 11 units of Intensive Reading material based on the previous needs analysis data. It covers the descriptive, narrative, recount, and procedure text materials, as those types of text are supposed to be taught in the Intensive Reading class. Moreover, materials related to the intensive reading skills such as scanning, skimming, previewing, predicting, building a powerful vocabulary, context clues, and understanding topic, main idea, and paragraph are also included in the final product. The Intensive Reading materials were validated by two experts and will be tried out to the second-semester students and three English lecturers in the English Language Education Program of Universitas Brawijaya Malang.